Investigative opportunities from smart heating technology: a preliminary evaluation - Horsman, Graeme (Taylor & Francis, 2025)
This work provides a case study documenting one of the first digital forensic examinations of a smart home heat system – Hive. The case study tries to address the forensic questions that law enforcement are likely to have in regards to smart home heating systems as well as highlighting relevant digital investigative opportunities. Data extracted from the Hive smart heating app (v. 10.54.2 (3)) when used on iOS v. 14.2 is presented and evaluated in order to determine whether it is possible to understand who has control over a heating system and what their controlling actions look like in regard to operating the system. Findings show that user information, pincode details and records of how the heating and water functionality can be acquired.
Keywords: Smart heating; digital forensics; investigation; digital evidence